Enantiopure 2-(2-ethylhexyl)dinaphtho[2, 3-b:2′, 3′-f]thieno[3, 2-b]thiophenes: synthesis, single-crystal structure and a surprising lack of influence of stereoisomerism on thin-film structure and electronic properties. Issue 1 (17th November 2021) - Sumitomo, Kenta; Sudo, Yuta; Kanazawa, Kiseki; Kawabata, Kohsuke; Takimiya, Kazuo
Abstract : Starting from a chiral resolution of 2-ethylhexanoic acid followed by conversions of functional groups without interfering with the enantiopurity, we have successfully introduced an enantiopure 2-ethylhexyl group on to dinaphtho[2, 3- b :2′, 3′- f ]thieno[3, 2- b ]thiophene (DNTT) via a Negishi-coupling reaction to synthesize 2-( R )-(2-ethylhexyl)- and 2-( S )-(2-ethylhexyl)-DNTT ( R - and S -EH-DNTT, respectively). Abstract : Starting from a chiral resolution of 2-ethylhexanoic acid followed by conversions of functional groups without interfering with the enantiopurity, we have successfully introduced an enantiopure 2-ethylhexyl group on to dinaphtho[2, 3- b :2′, 3′- f ]thieno[3, 2- b ]thiophene (DNTT) via a Negishi-coupling reaction to synthesize 2-( R )-(2-ethylhexyl)- and 2-( S )-(2-ethylhexyl)-DNTT ( R - and S -EH-DNTT, respectively). Then, the crystallinities, thin-film structures, and the organic field-effect transistors (OFETs) based on R -, S - and racemic EH-DNTT ( rac -EH-DNTT) were studied to elucidate the effect of stereoisomerism in the 2-ethylhexyl group. The crystal structures of the R - and S -EH-DNTTs are classified as herringbone packing and contain two crystallographically independent molecules connected by edge-to-face CH–π intermolecular interactions, and the molecules' directly opposite directions avoid steric repulsion between the 2-ethylhexyl groups. Thin films of the EH-DNTTs fabricated using both the spin-coating and vacuum-deposition methods were revealed to have similar but slightly different packing structures to that in the single crystal. Intriguingly, the packing structures in the thin-film state depend on the deposition method, and not on the stereoisomers of EH-DNTT. Consistent with the packing structures in the thin-film state, the performance of OFETs based on the thin films of the R -, S - and rac -EH-DNTTs were affected by the deposition method, and not by the stereoisomerism. This means that the stereoisomerism in the alkyl side chain has a marginal effect on the packing structure and electronic properties in the thin-film state. This is endorsed by the theoretical calculations using the functional-group symmetry-adapted perturbation theory (F-SAPT), which indicated that the intermolecular interactions between the DNTT cores are dominant in the total intermolecular interaction energies, and implies that the crystallization process in the thin-film deposition could be governed by intermolecular interactions between the DNTT cores. We conclude that in 2-ethylhexyl-substituted organic semiconductors with a large and highly aggregative π-conjugated core, like EH-DNTT, the enantiopurity in the 2-ethylhexyl group does not significantly affect the thin-film structure and thus the performance of thin-film OFETs.